Studi Literatur: Tanaman yang Memiliki Aktivitas Peluruh Kalsium Batu Ginjal Secara In Vitro - Yustika Rahayu; Nur Mita; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Kidney stones are a disease that is often found in society due to various causes. This disease is characterized by hardened deposits in the kidneys, mostly containing calcium oxalate and calcium phosphate. The medical treatment used is most effective with surgery. But this can carry significant risks, unwanted side effects, and is relatively expensive. So that herbal medicine becomes an alternative. This study aims to determine which plants have the activity of calcium kidney stone breaking. The research method used is online data search using appropriate keywords, carried out online in indexed journal databases. Based on several studies, there are several plants that have in vitro activity so that they can provide an overview of certain herbal plants that have the potential to decay calcium kidney stones, namely Cocor Bebek (Bryophyllum Pinnatum Lam), Kelor Leaves (Moringa oleifera Lam.), combination of Soursop Leaves ( Annona muricata) and pegagan (Centella asiatica L.Urb) , Adam Hawa leaves (Rhoeo discolor Hance), starfruit leaves (Averrhoa bilimbii L.), Moonflower leaves (Tithonia diversifolia), and celery (Apium graveolens L.)The part of tamanan leaves studied has a good affinity for releasing kidney stones calcium.